CONVENTIONAL AND IN SITU GEOCHRONOLOGY OF THE TEPLÁ CRYSTALLINE UNIT, BOHEMIAN MASSIF: IMPLICATIONS FOR THE PROCESSES INVOLVING MONAZITE FORMATION - Timmermann H.; Dörr W.; Krenn E.; Finger F.; Zulauf G. (My University, 2006)
The Teplá Crystalline unit (TCU), western Bohemian Massif, proves highly suitable for studying the effects of differential metamorphic reworking on the U–Th–Pb systematics in monazite, as the overprint of Variscan regional metamorphism onto high-grade Cadomian paragneisses intensifies progressively towards the northwest. Although variably hampered by scarcity, small size, and low uranium contents of monazite, isotope dilution–thermal ionisation mass spectrometry of monazite from paragneisses from the garnet, staurolite, and kyanite zones of the TCU gives a narrow 206Pb/238U age range from 387 to 382 Ma for Variscan peak metamorphism. These data are supported by 382–373 Ma monazite ages derived from electron microprobe analyses. Inheritance of older components in grains from the central TCU imply major “resetting” of pre-Variscan monazite around 380 Ma, possibly due to widespread garnet growth during Variscan metamorphism, which led to the consumption of pre-Variscan high-Y monazite and subsequent growth of new low-Y monazite. Concordant 498–494 Ma monazite ages in a migmatitic paragneiss close to the adjacent Mariánské Lázně Complex (MLC) grew in response to metagabbro emplacement in the MLC from 503 to 496 Ma and not during either Cadomian or Variscan regional metamorphism. Backscatter imaging and electron microprobe analyses reveal that discordant monazite of the migmatite comprises a mix of various age domains that range from ca. 540 to 380 Ma. Combined evidence presented here suggests that instead of Pb loss by volume diffusion, the apparent resetting of the U–Th–Pb systematics in monazite rather involves new crystal growth or regrowth by recrystallisation and dissolution/reprecipitation.
Keywords: U-PB GEOCHRONOLOGY ELECTRON MICROPROBE ANALYSIS; MONAZITE; TEPLÁ CRYSTALLINE UNIT; BOHEMIAN MASSIF